Impact of entrepreneurship education effectiveness towards graduate employability / Hardy Loh Rahim, Zanariah Zainal Abidin and Hardi Emrie Rosly. - Loh Rahim, Hardy; Zainal Abidin, Zanariah; Rosly, Hardi Emrie (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
The issue of graduate employability has been a point of discussion for many years. The high unemployment figure all over the world has somehow affected graduates of higher education institutions, as jobs are harder to get and employers can afford to be more selective. Employers look for other skills in graduates, more than just the basic knowledge of the graduates’ field of study. Research has shown that entrepreneurship education enhances skills sought after by employers. Therefore, this study looked into the relationship between entrepreneurship education effectiveness and the skills needed for graduate employability in an effort to further study whether entrepreneurship education does have a positive impact on graduate employability. The study was analyzed using structural equation modelling (SEM), involving 200 university students in Malaysia. The result indicated positive significant relationship between entrepreneurship education effectiveness and the skills needed for graduate employability.